23. IDENTIFIKASI PARASIT PADA IKAN LELE DUMBO (Clarias gariepinus) DI DESA LAMBRO DEYAH KECAMATAN KUTA BARO KABUPATEN ACEH BESAR Identification of Parasites in Catfish (Clarias gariepinus) in Lambro Deyah Kuta Baro Aceh Besar - Adistya Putra Rizki; Yudha Fahrimal; Razali Daud; T. Fadrial Karmil; Muhammad Hambal; Zuhrawati Z (Jurnal Medika Veterinaria, 2016)
The study aimed at identifying the types of parasites that infect catfish as well as to determine the prevalence of the parasite species. A total of 30 catfish were collected using nets then examined at Parasitology Laboratory, Veterinary Medicine Faculty, Syiah Kuala University Banda Aceh. Ectoparasites examination was carried out by directly observed the outer surface of fish body and by mucus smear examination microscopically. While endoparasites examination was done by observation on the inner surface of the digestive tract. The study revealed that five types of parasites infected catfish were Dactylogyrus (43.33%), Gyrodactylus (20%), Tricodina (3.33%), Camallanus sp (3.33%), and unidentified worm (3.33%). ____________________________________________________________________________________________________________________ Key words: catfish, ectoparasite, endoparasite